2021
DOI: 10.1029/2020ja028607
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic Activity Effects on CO2‐Driven Trend in the Thermosphere and Ionosphere: Ideal Model Experiments With GAIA

Abstract: We examine impacts of geomagnetic activity (GA) on CO2‐driven trend in the ionosphere and thermosphere using the Ground‐to‐topside Atmosphere Ionosphere model for Aeronomy whole atmosphere model. The model reveals three salient features. (1) Geomagnetic activities usually weakens the CO2‐driven trend at a fixed altitude. Among the IT parameters analyzed, the thermosphere mass density is the most robust indicator for CO2 cooling effect even with GA influences. (2) Geomagnetic activities can either strengthen or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
(66 reference statements)
1
9
0
Order By: Relevance
“…Between 20° and 60 𝐴𝐴 • S above ∼220 km altitude, the ion density decreased by 50% at maximum. These responses of the ion density are consistent with previous model studies and observations (Danilov & Konstantinova, 2013;Laštovička et al, 2008;H. Liu et al, 2021;Ogawa et al, 2014;Qian et al, 2009;Zhang & Holt, 2011).…”
Section: Strengthening Of Zonal Ion Drag Force and Meridional Pressur...supporting
confidence: 92%
See 1 more Smart Citation
“…Between 20° and 60 𝐴𝐴 • S above ∼220 km altitude, the ion density decreased by 50% at maximum. These responses of the ion density are consistent with previous model studies and observations (Danilov & Konstantinova, 2013;Laštovička et al, 2008;H. Liu et al, 2021;Ogawa et al, 2014;Qian et al, 2009;Zhang & Holt, 2011).…”
Section: Strengthening Of Zonal Ion Drag Force and Meridional Pressur...supporting
confidence: 92%
“…The z-coordinate (height) is preferred over the pressure coordinate for ionosphere/thermosphere studies not only because it facilitates comparison with observations (mostly made at certain heights), but also because the ionosphere and the ion drag (the most important factor in the upper atmosphere) are better organized with height. Many studies on the long-term trend in the ionosphere/thermosphere have been carried out in z-coordinate, for example, Keating et al (2000), Emmert, Picone, et al (2004), Emmert, Fejer, et al (2004, Marcos et al (2005), Saunders et al (2011), Solomon et al (2015, Cnossen (2020), H. Liu et al (2020), and H.-L. Liu et al (2021).…”
Section: Momentum Balance In the Thermospherementioning
confidence: 99%
“…We set a constant solar minimum condition in this work, but how the EPB occurrence changes with increasing anthropogenic emissions under different solar conditions still needs investigation. In addition, as H. Liu et al (2021) reported, geomagnetic activity could strengthen or weaken CO2-driven climate change in the upper atmosphere. The ionospheric long-term trend is also influenced by geomagnetic activity (Mikhailov & Marin, 2000; S. R. Zhang & Holt, 2013).…”
Section: Resultsmentioning
confidence: 88%
“…Considering the CO 2 variability, Cnossen (2020) analyzed the long-term database of WACCM-X using a modified regression method to examine the impact of CO 2 and geomagnetic field changes on upper atmosphere climate change. Based on a whole atmosphere model, GAIA, the CO 2 doubling effect in the upper atmosphere and the dependence of geomagnetic activity upon the CO 2 -driven trend have been investigated recently (Liu HX et al, 2020, 2021. Nonetheless, to our knowledge, the interaction between CO 2 change and geomagnetic field variation has not been investigated before.…”
Section: Introductionmentioning
confidence: 99%